Firebugs - Bulling, Nino 1986- (Drawn & Quarterly, 2024)
Everything is changing-but everything is also exactly the same. Ingken can't ignore it: ice caps stained brown from forest fires, pipeline construction, drought... the whole world somehow persists despite the slow erosion of stability. After a trip to Paris, Ingken returns home ready for a break from drugs. Their supportive partner, Lily, is flushed, excited about a new connection she's made. Although Ingken wants to be happy for her, there's a discomfort they can't shake. Sleepless nights fill with an endless scroll of images and headlines about climate disaster. A vague dysphoria simmers under their skin; they are able to identify that like Lily, they are changing, but they're not sure exactly how and at what pace. Everyone keeps telling them to burn themself to the ground and build themself back up but they worry about the kind of debris that fire might leave behind. Nino Bulling's artwork is immediately familiar. Like a conversation with a good friend, their story is told as quiet as it can be loud. Crowds and landscapes squiggle in expressive black and white. Red cuts through panels with energy and persistence, bringing life to what might seem dead. In its most intimate moments, Firebugs asks what it means to transition in a transitioning world
Keywords: Umweltveränderung; Transgender; Nichtbinäre Geschlechtsidentität; Umweltschaden; Transgender people / Comic books, strips, etc; Gender transition / Comic books, strips, etc; Environmental degradation / Comic books, strips, etc; Global environmental change / Comic books, strips, etc; Human ecology / Comic books, strips, etc; Gender-nonconforming people / Comic books, strips, etc; Gender identity / Comic books, strips, etc; Environmental degradation; Global environmental change; Human ecology; Gender-nonconforming people; Gender identity; Germany / https://id.oclc.org/worldcat/entity/E39PBJtCD3rcKcPDx6FHmjvrbd; Transitioning (Gender); Non-binary people; Transgender people; LGBTQ+ people; Graphic novels; Comics (Graphic works); Non-binary comics; LGBTQ+ comics; Transgender comics; Queer comics; Comic